The Mystery We Celebrate, the Song We Sing : A Theology of Liturgical Music - Harmon, Kathleen A., 1944- (Book collections on Project MUSE., 2008)
"Music and liturgy seem inseparable, yet we seldom pause to ponder their relationship in depth. In this volume, Kathleen Harmon offers her own insights by creatively exploring the complex interplay between congregational singing and the liturgical celebration of the paschal mystery. Harmon asserts that liturgical music, in the form of communal singing, is a vehicle through which the ritual reenactment of the paschal mystery is effected. She addresses concrete and practical pastoral applications of the relationship between music and liturgy. She focuses on how the liturgical singing of the assembly creates the collective consciousness of church as the Body of Christ. Music, then, is much more than just a component of liturgy; it is, in Harmon's view, absoltely constitutive both of liturgy's deepest essence and its fullest realization." -- Back cover.